Optimal Permissible Placement by the Height of the Transitive Directed Tree with One Root - Khachaturyan, Armen (Mathematical Problems of Computer Science, 2021)
In paper [1] we have introduced a new concept – the transitive directed tree with one root and have formulated its minimum permissible placement problem by the height. In the papers [1] and [2] we have introduced a couple of new concepts and obtained necessary conditions for the solution of that problem. In the present paper using the results and the introduced concepts from the papers [1] and [2] we obtain an optimal polynomial algorithm for the problem solution and present the proof of its optimality.